Soil-Water Characteristics and Creep Deformation of Unsaturated Expansive Subgrade Soil: Experimental Test and Simulation - Yao, Yongsheng; Li, Jue; Xiao, Ziqiong; Xiao, Hongbin (Frontiers in Earth Science, 2021)
The creep deformation of expansive soil has been considered as a vital threat to the safety in engineering construction because it may cause serious slope diseases in geological engineering. Meanwhile, since expansive soil usually remains in unsaturated state, its mechanical property is significantly affected by the seasonal environment. Therefore, the nonlinear deformation of expansive soil has received increasing attention, especially the humidity-dependent creep properties. This study focused on the stability of the unsaturated expansive soil subgrade considering rainfall and the creep behavior. Pressure plate extractor and direct shear tests were performed to investigate the hydro-mechanical and creep characteristics of the unsaturated expansive soil. Both the Van-Genuchten and Burgers models were applied to analyze the test results and inserted into the numerical model of the slope under rainfall infiltration. Results show that the compaction degree and the stress state was closely related to the water holding capacity of the expansive soil. The nonlinearity of the creep behavior became increasingly obvious with the increase of time and the stress level. The safety factor of the slope decreased as the rainfall time increased, and the most dangerous slide of the slope moved toward the foot of the slope. Considering the long-term creep process, there was a period of rapid growth in horizontal displacement that is detrimental to the stability of the slope. Besides, the rainfall infiltration could accelerate the slope failure before and after this creep process.